The Influence of Parents' Digital Communication on the Mental Health of Students Living Away from Home - Abdillah Lathief Al Habib; Tri Suminar (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the effect of digital communication between parents and students on the mental health of students living away from home at the Faculty of Education and Psychology, Semarang State University. This study uses a quantitative approach with simple linear regression analysis techniques. The results of the test show that digital communication between parents has a positive and significant effect on the mental health of students who live far from their family environment. Consistent and high-quality digital communication is one of the factors that plays an important role in maintaining the psychological stability of students living away from home. These findings have implications for the development of digital media-based family interaction patterns as a strategy to support the mental health of students who are far from their parents.